Sickle cell disease: acute clinical manifestations in early childhood and molecular characteristics in a group of children in Rio de Janeiro - Silva Filho,Isaac Lima da (2012)
OBJECTIVE: To describe clinical events of sickle cell disease and the correlation with β-globin haplotypes and α-thalassemia in under 6-year-old children. METHODS: A retrospective study was conducted of under 6-year-old children from the neonatal screening program in Rio de Janeiro. Forty-eight male and 48 female children were enrolled in this study, 79 with sickle cell anemia and 17 with hemoglobin SC. The mean age was 29.9 (standard deviation = 20.9) months, 62 (16.2 ± 8.6) were aged between 0-3 years old and 34 (54.9 ± 11.3) were from 3-6 years old. Painful events, acute splenic sequestration, hemolytic crises, hand-foot and acute chest syndromes and infections were evaluated. RESULTS: The events were more frequent in under 3-year-old children, 94% of children had at least one episode. Infection was the most common event affecting 88.5% of children. Acute splenic sequestration took place earlier, while painful crises and acute chest syndromes in under 6-year-old children. Thal-α 3.7 was observed in 20.9% of cases. Bantu was the most frequent haplotype found, followed by Benin. No correlation was observed between clinical events and β-globin haplotypes. Children with sickle cell anemia and α-thalassemia have less infectious events. No correlation was found among these polymorphisms and clinical events, however, the majority of children with Bantu/Bantu and without α-thalassemia had more clinical events.